Cash return on capital invested ten years of investment analysis with the CROCI economic profit model - Costantini, Pascal
In this book, Pascal Costantini gives a lively and wonderfully readable account of ten years of efforts by a small group of investment analysts to find a reliable, practical and implementable method for valuing and selecting shares. The result of their effort is an original investment methodology called CROCI (Cash Return on Capital Invested). For over a decade now, Costantinis group at Deutsche Bank has been using this valuation tool every time it has had to take a view on the pricing of an equity asset, be it a market, a sector or an individual sharein other words, every single working day.